Standards for Facilities and Infrastructure in Building Quality Education in Senior High Schools - Khairullah, Ridho; Fatayan, Arum; Syarif, Moh Suryadi; Ghani, Abd. Rahman A (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The intent of this study is to evaluate and measure the gaps in various components—design, installation, process, and product—so that it can provide information for improvement and development related to the Facilities and Infrastructure Standards in Building Educational Quality at Senior High School. The evaluation model approach used in this study is the Discrepancy Evaluation Model, developed by Malcolm Provus. This research method is a mixed method, not only qualitative, descriptive, and evaluative but also quantitative, and it combines both. The evaluation subjects were 12 people, including principals, vice principals, educators, parents, committees, and supervisors at Fatahillah Ciledug Senior High School, Tangerang City. The evaluation findings indicate that the gap or discrepancy in the design aspect is 70% according to the standard indicators of facilities and infrastructure, based on the reference criteria categorized as